2009
DOI: 10.1111/j.1365-2699.2008.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seed dispersal and pollen flow inQuercus garryana(Fagaceae) following post‐glacial climatic changes

Abstract: Aim We examined the genetic structure of Quercus garryana to infer post-glacial patterns of seed dispersal and pollen flow to test the hypotheses that (1) peripheral populations are genetically distinct from core populations and from one another; (2) genetic diversity declines towards the poleward edge of the species' range; and (3) genetic diversity in the chloroplast genome, a direct measure of seed dispersal patterns, declines more sharply with increasing latitude than diversity in the nuclear genome. We ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 73 publications
2
38
2
1
Order By: Relevance
“…In general, signs of population isolation and low gene flow were detected throughout the Central System (F ST = 0.239) compared to that reported for some other wind-pollinated temperate forest species: F ST = 0.049 in Quercus garryana Douglas ex Hook [64], F ST = 0.052 in Populus euphratica Olivier [65], Φ ST = 0.013 in Fraxinus excelsior L. [66], and F ST = 0.074 in Castanea sativa Mill. [67].…”
Section: Genetic Diversity and Population Relationshipmentioning
confidence: 57%
“…In general, signs of population isolation and low gene flow were detected throughout the Central System (F ST = 0.239) compared to that reported for some other wind-pollinated temperate forest species: F ST = 0.049 in Quercus garryana Douglas ex Hook [64], F ST = 0.052 in Populus euphratica Olivier [65], Φ ST = 0.013 in Fraxinus excelsior L. [66], and F ST = 0.074 in Castanea sativa Mill. [67].…”
Section: Genetic Diversity and Population Relationshipmentioning
confidence: 57%
“…Similar results were reported by Castagneyrol et al (2012), who found that the genetic attributes of the host plant (genetic diversity, kinship, and genetic identity) had no significant effect on the community of phytophagous insects (endophagous and ectophagous) associated with the canopy of Q. robur in France. The absence of a response by the canopy communities associated with Q. robur in Europe is probably due to the lower levels of genetic diversity of European species (whose populations were affected by glaciations) compared to the diversity reported for Mexican oak species (i.e., Magri et al 2007;Marsico et al 2009). Vakkari et al (2006) reported very low levels of genetic diversity (He = 0.162) of Q. robur in Finland.…”
Section: Reviewmentioning
confidence: 95%
“…Most previous studies of oak species using cpDNA markers have found similar high differentiation levels and a clear geographic segregation of haplotypes lineages, which are usually explained by the historical migration patterns of the populations and the very low dispersal capacity of acorns (Magni et al 2005;Grivet et al 2006;Magri et al 2007;Marsico et al 2009). However, in Q. deserticola the distribution of haplotypes was rather patchy, displaying strong local genetic structure but without obvious phylogeographic breaks, contrasting with some previous studies in the TMVB that have found a west-east LGM, and the MIROC model suggested a modest eastwards expansion from the LGM to the present along the TMVB.…”
Section: Phylogeographic Structure and Demographic Historymentioning
confidence: 97%